(untitled) (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2026)
At first glance, the present issue of Studia Universitatis Babeș–Bolyai, Theologia Reformata Transylvanica may appear remarkably diverse. The studies take us across different historical periods, geographical settings, and academic disciplines: from the memory of ancient Jerusalem to the history of the Korean ecumenical movement and from the historical traumas of Central Europe to the question of reconciliation in post-genocide Rwanda. Despite the diversity of topics, however, the contributions are connected by a common question: how do the experiences of the past continue to live on in the memory of individuals and communities, and what paths may lead towards healing or reconciliation? The authors approach this broad field of inquiry through different methods and perspectives. Some examine the relationship between memory and identity through the interpretation of biblical texts, while others explore the possibilities of reconciliation through the analysis of historical events or ecclesiastical processes. Several studies also demonstrate that coming to terms with the wounds of the past is not merely a task for historians or social scientists but a theological challenge as well. A Studia Universitatis Babeș–Bolyai, Theologia Reformata Transylvanica jelen száma első pillantásra rendkívül sokszínűnek tűnhet. A tanulmányok különböző korokba, földrajzi terekbe és tudományterületekre vezetnek el bennünket: az ókori Jeruzsálem emlékezetétől a koreai ökumenikus mozgalom történetéig, a közép-európai történelmi traumáktól a ruandai népirtás utáni megbékélés kérdéséig. A témák változatossága ellenére az írásokat mégis összeköti egy közös kérdés: miként élnek tovább a múlt tapasztalatai az egyének és közösségek emlékezetében, és milyen utak vezethetnek a gyógyulás vagy a kiengesztelődés felé. A szerzők eltérő módszerekkel és eltérő nézőpontokból közelítenek ehhez a problémakörhöz. Van, aki bibliai szövegek értelmezésén keresztül vizsgálja az emlékezet és az identitás kapcsolatát, mások történelmi események vagy egyházi folyamatok elemzésével keresik a megbékélés lehetőségeit. Több tanulmány arra is rámutat, hogy a múlt sebeinek feldolgozása nem csupán történészi vagy társadalomtudományi feladat, hanem teológiai kihívás is.